Isolation, identification and antimicrobial activities of Lactic Acid Bacteria from fruits of wild plants in Tambrauw Forest, West Papua, Indonesia - Achmad Dinoto; A’liyatur Rosyidah; Anggi Ria Puspitasari Susilo; Heddy Julistiono (Society for Indonesian Biodiversity, 2020)
Abstract. Dinoto A, Rosyidah A, Susilo ARPS, Julistiono H. 2020. Isolation, identification and antimicrobial activities of Lactic Acid Bacteria from fruits of wild plants in Tambrauw Forest, West Papua, Indonesia. Biodiversitas 21: 3391-3397. Presence of culturable lactic acid bacteria (LAB) in fruits of wild plants and their antimicrobial activities has not been widely reported. The purposes of this study were to isolate LAB from the fruits of wild plants found in the Tambrauw forest area, West Papua Indonesia, and to evaluate their antimicrobial activities. Isolation of LAB from fruit was conducted using MRS medium supplemented with 1% CaCO3. Isolates of LAB were identified based on 16S rRNA gene using BLAST analysis. Antimicrobial assays were carried out by determining the minimum inhibitory concentration (MIC) based on thiazolyl blue tetrazolium blue (MTT) using indicator microorganisms Escherichia coli, Staphylococcus aureus, and Mycobacterium smegmatis. The results showed that total of fourteen isolates of LAB with different characteristics was successfully isolated from 8 of 14 collected wild plants. Based on 16S rRNA sequences, isolates had closest relationships with Lactococcus lactis, Lactococcus garvieae, Weissella confusa, Weissella oryzae, and Enterococcus faecalis with the similarity of 99%. All 16S rRNA nucleotides of these strains have been deposited in the GenBank. Assays for antimicrobial activities were demonstrated by the highest inhibition of supernatant of Lac. lactis HM 1.1 from fruit plant Donax canniformis and W. confusa H14.2 from fruit plant Capparis sp. against E. coli, S. aureus, and M. smegmatis even though the MIC values of those strains were lower than that of bacterial strain from the commercial probiotic product. This study showed that wild fruit from Tambrauw forest harbor beneficial lactic acid bacteria that could be important for health of animals and humans as well. In addition, this study provided basic information on indigenous LAB for promoting further development of medicinal antibacterial compounds.